Raising a Market Show Hog - Chris DeCubellis (EDIS)
One of the most rewarding and educational 4-H projects is raising, finishing, and showing a market hog. Many younger 4-H’ers excitedly wait until the day when they can choose their first show pig. Parents and youth need to understand that while the hog project is an excellent opportunity, it requires a great deal of thought, preparation, time, and resources. The purpose of this new 7-page publication is to help parents and youth understand some of the commitments and preparations involved in raising a hog, as well as what to expect and what to do in order to successfully complete the project. Written by Chris DeCubellis and published by the UF/IFAS 4-H Youth Development Program. https://edis.ifas.ufl.edu/4h407